Способ регулирования температуры в греющей камере печи и система для его реализации - Букреев В. Г. Виктор Григорьевич; Васичкин Ю. И. Юрий Иванович; Кладиев С. Н. Сергей Николаевич; Кокорев С. В. Сергей Валерьевич; Пищулин В. П. Владимир Петрович; Руль А. И. Александр Иванович; Цхе А. В. Алексей Викторович
опубл. 27.08.07